The biomechanics of the track and field sprint start: a narrative review - Neil Bezodis (Sports Medicine, 2019)
The start from blocks is a fundamental component of all track and field sprint events (≤ 400 m). This narrative review focusses on biomechanical aspects of the block phase and the subsequent first flight and stance phases. We discuss specific features of technique and how they may be important for a high level of performance during the start. The need to appropriately quantify performance is discussed first; external power has recently become more frequently adopted because it provides a single measure that appropriately accounts for the requirement to increase horizontal velocity as much as possible in as little time as possible. In the “set” position, a relatively wide range of body configurations are adopted by sprinters irrespective of their ability level, and between-sprinter differences in these general positions do not appear to be directly associated with block phase performance. Greater average force production during the push against the blocks, especially from the rear leg and particularly the hip, appears to be important for performance. Immediately after exiting the blocks, shorter first flight durations and longer first stance durations (allowing more time to generate propulsive force) are found in sprinters of a higher performance level. During the first stance phase, the ankle and knee both appear to play an important role in energy generation, and higher levels of performance may be associated with a stiffer ankle joint and the ability to extend the knee throughout stance. However, the role of the sprinter’s body configuration at touchdown remains unclear, and the roles of strength and anatomy in these associations between technique and performance also remain largely unexplored. Other aspects such as the sex, age and performance level of the studied sprinters, as well as issues with measurement and comparisons with athletes with amputations, are also briefly considered.